Identification of mycosporinelike amino acids and 3-dehydroquinate synthase gene expression in UV radiation-induced Deinococcus radiodurans R1 - Huwaidi, Alaa Hassan Ibrahim Ahmed (2018)
Deinococcus radiodurans R1 is a well-known heterotrofic bacterium with extreme radio-resistant capability. It exhibits radiation survival up to 15,000 Gy while still be able to grow normally at 60 Gy/h. The radiation-tolerant mechanism that involves DNA repair represents 20% of the total resistant mechanism. Meanwhile, the other 80% comes from antioxidants. Since D. radiodurans R1 was discovered in 1956, the whole radio-resistant mechanism is not yet fully understood. Mycosporine-like amino acids (MAAs) are a group of 40 or more compounds that have antioxidant, growth stimulation and UV protective properties found in many microorganisms. In D. radiodurans R1, 3-dehydroquinate synthase (DHQ) gene annotated in chromosome 1 encodes the precursor for all MAAs. In this study, a significant amount of MAAs was found in D. radiodurans R1 after treatment with a different type of UV radiations, namely; UVA (360 nm) 6W and 100 W, and UVC (254 nm) 6W at a period of 12 to 48 hours. The RNA and MAAs were isolated from the UV-treated D. radiodurans R1. RT-qPCR experiment of the DHQ gene resulted in a significant increase in the number of expression fold from 4 to 9273 fold. Consequently, specific MAAs were identified using time-of-flight mass spectrometry (TOF-MS). They are mycosporinetaurine, mycosporine-glutamine, mycosporine-glutaminol, mycosporine-glutaminolglucoside, mycosoprine-glycine, mycosporine-2-glycine, mycosporineglycine: glutamic acid, shinorine, mycosporine-methylamine:serine, palythine-serine, and palythinol. The results suggested that these compounds play essential roles in D. radiodurans R1 radio-tolerance especially Mycosporine-methylamine:serine and palythine-serine for its expression at every UV treatment. This study may well help to understand radiation resistance mechanism further, and it is potential to be utilized as human protective compound against radiation risk.